ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH PT BANK BUKOPIN CABANG JEMBER - Agung Dwi Hermawan, Agung Dwi Hermawan; Ageng Pratiwi, Ageng Pratiwi; Yudhitia dian Putra, Yudhitia dian Putra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Bank Bukopin is one of the banks that makes service a top priority in building its image in the community. As a private bank that is still growing, Bank Bukopin has been able to survive in the face of competition in the banking world to date. In addition, judging from the number of customers or the growth of Third Party Funds, Bank Bukopin is still below other large banks, thus making Bukopin still have to consistently and continuously improve services that are different from other banks to build customer loyalty and increase the growth of third party funds. The increasingly fierce competition in the business world at this time, makes business actors, whether individuals or partnerships, or in the form of companies, must have factors that can be used by companies as weapons in their efforts to win the competition with their competitors in the business world. has tried to compete and provide the best for consumers, it may not necessarily guarantee the success of efforts to achieve company goals, because each consumer has different tastes and desires, so each company has a different service strategy. Likewise in the world of banking, service strategy is one of the important factors in increasing customer satisfaction and loyalty and improving the image of the company itself because banks as financial service providers are very dependent on customers or customers who use their services.